RAISING VOICES FOR PALESTINE: ANALYZING MACKLEMORE’S "HIND’S HALL" THROUGH BARTHES' SEMIOTIC LENS - Sujiwa, Krisna; Zulferdi, Lazuar Azmi (Rubikon : Journal of Transnational American Studies, 2026)
This study examines Macklemore’s 2024 protest song “Hind’s Hall” as a cultural text that articulates transnational solidarity with Palestine amid escalating global attention to the Israeli–Palestinian conflict. While popular music has long functioned as a medium of political expression, scholarly analyses of contemporary Western protest songs addressing this issue remain limited. The research investigates how the song’s lyrics and visuals construct meanings related to resistance, institutional repression, and global activism. Grounded in Roland Barthes’ semiotic theory, particularly the concepts of denotation and connotation, the study employs a qualitative method through close reading of lyrical content and selected scenes from the music video. The findings reveal that denotative elements depict protest actions, state violence, and humanitarian suffering, while connotative meanings expose deeper ideological critiques of colonialism, racial capitalism, media manipulation, and the criminalization of dissent. The song also mobilizes affect and empathy to foster a sense of collective responsibility and transnational unity. This study concludes that “Hind’s Hall” operates not merely as a protest anthem but as a layered cultural artifact that challenges dominant narratives and amplifies marginalized voices. By transforming personal expression into political discourse, the song demonstrates how contemporary music can function as a powerful instrument of global awareness and resistance.